PEMBUATAN VIDEO PELAYANAN KANTOR DESA SEKURA BERBASIS ANIMASI 2D - Ruri Rantika Sari; Milda Surgani Firdania; Noferianto Sitompul (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2022)
Sekura Village Office does not yet have the media to deliver the services at Sekura Village Office. The services at Sekura Village Office are in the form of population administration such as ID cards, family cards, birth certificates, marriages, deaths, and business permits. Information about services at Sekura Village Office has not been visualized properly. Currently, the information can be obtained by coming directly to the village office. Therefore, a 2D animated video was made entitled Keluarge Pak Wawan di Kantor Desa Sekura, which can provide information for the community about services at Sekura Village Office. This study aims to provide information about the services of Sekura Village Office so that it is better known to the public, especially the Sekura Village area in the form of 2D animation. The development method that will be used in making 2D animation is the Villamil-Molina method. This development method consists of 3 stages, namely Pre Production, Production, and Post Production. The results of this study are 2D animation in MP4 format.